Penyuluhan Public Speaking dan Pendidikan Antikorupsi sebagai Upaya Pembentukan Karakter Siswa SMK Manba'ul 'Ulum Babelan - Anggita Gyarani; Endah Prawesti Ningrum; Hidayat Nur Prayogi; Tubagus Adiansyah; Nailah Nurul Qalbina; Sayyidah Fatma Azzahra; Naila Joan Apriliani; Devina Alfiani; Annisa Nurullita; Nayla Pungky Ermiyani; Riski Nurgiono; Hafizd Saifulloh Mufid; Martua Nehemia Sebastian; Syafiq Musyafa; Rimzha Firmansyah; Vina Rusita Damayanti (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
This community service activity aimed to improve students' understanding of anti-corruption values and enhance public speaking skills as an effort to strengthen character education among students at SMK Manba'ul 'Ulum, Buni Bakti Village, Bekasi Regency. The activity was conducted based on the identification of students' limited confidence in expressing ideas publicly and insufficient awareness regarding anti-corruption attitudes and behaviors in daily life. The program was implemented by the KKN Group 51 Team of Universitas Bhayangkara Jakarta Raya on June 3, 2026, involving 50 eleventh-grade students in anti-corruption education and 20 members of the student council (OSIS) in public speaking training. The methods applied included lectures, interactive discussions, question-and-answer sessions, ice breaking activities, and practical exercises. The results indicated increased understanding of corruption prevention, integrity values, and responsible behavior. Furthermore, public speaking training improved students' confidence, communication skills, and ability to convey ideas systematically. The integration of anti-corruption education and public speaking practice effectively supported students' character development and encouraged the formation of responsible and communicative young generations.